Macro markets : creating institutions for managing society's largest economic risks - Shiller, Robert J. (Oxford : Clarendon Press ; New York : Oxford University Press, 1993)
it puts forward a unique and authoritative set of detailed proposals for establishing new markets for the management of the biggest economic risks facing society.
"Clarendon lectures in economics"--Jacket.
Includes bibliographical references (p. 228-240) and indexes.
uaj 25/02/2015
Loans
Keywords: Stock exchanges; Risk; Markets